STRESS, ANXIETY, AND DEPRESSION RELATIONSHIP AMONG UNDERGRADUATE MEDICAL STUDENTS AND THEIR FINAL EXAM MARK - Noerhidajati, Elly; Makarim, Fadhli Rizal; Albab, Akhmad Ulil (LIFE: International Journal of Health and Life-Sciences, 2018)
Medical students often experiencing a stressful environment in their medical school. Stress occurred in students that currently studying for examinations. Higher stressor expose leads to higher levels of anxiety and depression. High level of stress declines cognitive functioning and learning process in their medical academic process and cause mental health impairment. A prospective cross-sectional study with 26 end-stage medical students as a participant, the participant ordered to fill 3 section questionnaire that measures stress, anxiety, and depression. Final exam mark obtained from Indonesian Medical Education Institution Association (AIPKI) one month after the exam held. There is no significant relationship between stressor in all domain and anxiety, and there is a significant relationship between academic related stress, social related stress, and depression. There is no significant difference between stress, anxiety, depression and their final exam mark. In conclusion, there is a strong relationship between stress that leads to depression in undergraduate medical students. Therefore, a good coping mechanism of stress should be well managed in medical students.